Les problèmes de traduction posés par l’articulation Discours Direct / Récit - Lucie GOURNAY (E-REA)
This paper deals with some translation difficulties that arise in the framing of fictional dialogue. After studying a corpus of contemporary English novels and their published translation into French, we will argue that the difference between narration and direct speech is definitely more signaled in France than it is in English. More specifically, we will show that in French, the qualification of direct speech via He-said “verbal” sentences or She-shrugged “action” sentences is restrained to a strong objective point of view, thus explaining the change in the translation from English into French.